3D Printing and Digital Processing Techniques in Dentistry: A Review of Literature. Issue 6 (8th March 2019) - Lin, Liwei; Fang, Yingfeng; Liao, Yuxuan; Chen, Gang; Gao, Chunxia; Zhu, Peizhi
Abstract : In recent years, the rapid development of 3D printing technologies lead to its new applications in the area of healthcare and medicine, including dentistry, orthopedics, cardiovascular, pharmaceutics, neurosurgery, engineered tissue models, medical devices, and anatomical models. Dentistry is widely acknowledged to benefit from 3D printing technologies due to its needs for the customization and personalization of dental products. In this review, the authors discuss and summarize various 3D imaging technologies and the recent advances of 3D digital processing techniques in dentistry in an effort to give a new perspective and greater understanding of the current development of 3D printing technologies in dentistry. It is anticipated that this review will explore why 3D printing is important to dentistry, and why dentistry motivates development in 3D printing applications. Further, current challenges and further perspectives are also discussed which helps researchers to optimize the 3D printing technology in dentistry, improve 3D printing strategies, and direct future dental bioprinting and translational applications. Abstract : This article provides a comprehensive review of the recent development of 3D printing and 3D imaging technologies, and presents the recent advances of 3D printing in dentistry. Meanwhile, current challenges and further perspectives are also discussed which will benefit researchers to optimize the 3D printing technologies and strategies in dentistry, directing the future trend of the dental development.